Beneficial Impact of an Extract from the Berries of Aronia melanocarpa L. on the Oxidative-Reductive Status of the Submandibular Gland of Rats Exposed to Cadmium - Adam Dąbrowski; Barbara M. Onopiuk; Halina Car; Paweł Onopiuk; Zofia N. Dąbrowska; Joanna Rogalska; Małgorzata M. Brzóska; Ewa Dąbrowska (MDPI AG, 2020)
Oxidative stress underlies the pathomechanisms of toxic action of cadmium (Cd), including its damaging impact on the oral cavity. This study investigated whether the administration of an extract from Aronia melanocarpa L. berries (AME), characterized by their strong antioxidative potential, may have a beneficial impact on the oxidative-reductive status of the submandibular gland in an experimental model of low-level and moderate human environmental exposure to cadmium. The main markers of the antioxidative status (glutathione reductase, superoxide dismutase, catalase, reduced glutathione, total antioxidative status (TAS)), total oxidative status (TOS), oxidative stress index (OSI = TOS/TAS), and lipid peroxides, as well as cadmium concentration, were evaluated in the submandibular gland tissue of female Wistar rats who received a 0.1% aqueous AME and/or a diet containing 0, 1, and 5 mg Cd/kg for 3 and 10 months. The treatment with cadmium decreased the activities of antioxidative enzymes (29%−74%), reduced glutathione concentration (45%−52%), and TAS and increased TOS, resulting in the development of oxidative stress and enhanced concentration of lipid peroxides in the submandibular gland. The administration of AME at both levels of exposure to cadmium offered significant protection against these actions of this xenobiotic. After the 10 month exposure to the 1 and 5 mg Cd/kg diet, TAS was decreased by 77% and 83%, respectively, TOS, OSI, and lipid peroxides concentration were increased by 50% and 52%, respectively, 11.8-fold and 14.4-fold, respectively, and 2.3-fold and 4.3-fold, respectively, whereas, in the case of the extract co-administration, the values of these parameters did not differ compared to the control group. The results indicate that the consumption of aronia products under exposure to cadmium may have a beneficial impact on the oxidative-reductive status of the submandibular gland and prevent oxidative stress development and enhanced lipid peroxidation in this salivary gland.